EFEK SMARTPHONE PADA PERKEMBANGAN MOTORIK KASAR ANAK USIA 4-6 TAHUN DI RT 36/RW 12 LILIBA, KECAMATAN OEBOBO KOTA KUPANG - Fera Ratna Dewi Siagian; Michael Johannes Hadiwijaya Louk; Jurdan Marthin Siahaan; Norberti Sigi (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2022)
In this study, researchers will find out howeffect of smartphones on gross motor development of children aged 4-6 years in RT 36/ RW 12 Liliba, Oebobo district, Kupang City. The purpose of this study was to determine the effect of smartphones on gross motor development of children aged 4-6 years. The method used in this study is a qualitative descriptive phenomenological approach with data collection techniques in the form of a questionnaire. The subjects of this study were the parents of children aged 4-6 years, totaling 31 respondents. The results of this study are where children in this case do gross motor movements or physical activities that they should do, but the consequences and addiction to playing smartphones are difficultfor children to talk to when they are busy playing their smartphones and difficulty to socialize with friends due to addiction to playing smartphones. The conclusion is that there is an effect of playing smartphones on children aged 4-6 years on gross motor development such as children cannot play outside the house, children become difficult to socialize with their friends, children like to be alone with their smartphones, in the absence of two-way communication.